Tolerance Behavior of Rural and Urban Communities in the Kampung Moderasi Beragama (KMB) Program in Banten Province - Khosiin Khosiin; Dwi Sadono; Siti Amanah (Lembaga Bale Literasi, 2026)
The increasing complexity of Indonesia’s social diversity reinforces the urgency of strengthening religious moderation at the community level. The existence of rural and urban areas with different social characteristics shapes diverse patterns of interaction and social cohesion, thereby influencing the practice of tolerance in everyday life. Acts of intolerance, particularly in Banten Province, are still found, especially in the form of rejection of the construction of houses of worship for other religions, which are driven by non-compliance with regulations, historical factors, and misunderstandings among religious groups. This condition indicates that the transformation of tolerance behavior has become an urgent necessity. This study aims to analyze the influence of individual profiles, internal factors (knowledge, motivation, and attitudes), and external support (role models, social group support, and religious extension support) on religious tolerance behavior, which is conceptualized through self-efficacy and tolerance practices. This study employs a quantitative approach using a survey method involving 155 married respondents across four villages/urban wards in Banten Province. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS), supported by interview results with community representatives and local leaders. The results show that internal factors have the strongest influence on religious tolerance behavior, followed by individual profiles and external support. These findings emphasize that efforts to enhance religious tolerance should focus on strengthening individuals’ internal capacities, while also fostering a conducive social environment to promote sustainable tolerance practices in both rural and urban communities in Banten Province.